Antimicrobial efficacy of drug blended biosynthesized colloidal gold nanoparticles from Justicia glauca against oral pathogens: A nanoantibiotic approach. (December 2017) - Emmanuel, Rayappan; Saravanan, Muthupandian; Ovais, Muhammad; Padmavathy, Sethuramasamy; Shinwari, Zabta Khan; Prakash, Periyakaruppan
Abstract: Antimicrobial resistance is a challenging task for researchers to develop new strategies. Green synthesis of AuNPs is an eco-friendly approach, which can be utilized in the microbistatic and microbicidal activities. The current study is focused on Justicia glauca (aqueous leaf extract) mediated AuNPs synthesis at room temperature by treating chloroaurate ions, that shows an antagonistic effect with Azithromycin (AZM) and Clarithromycin (CLR) antibiotics against oral pathogenic bacteria and fungi ( Micrococcus luteus, Bacillus subtilis, Staphylococcus aureus, Streptococcus mutans, Lactobacillus acidophilus, Escherichia coli, Pseudomonas aeruginosa, Saccharomyces cerevisiae and Candida albicans ). Characterization of green synthesized AuNPs was done by using Ultraviolet-visible (UV-vis) spectroscopy, Fourier Transform Infrared (FTIR) spectroscopy, Transmission Electron Microscopy (TEM), X-Ray Diffraction (XRD) analysis and Energy Dispersive X-ray analysis (EDAX). Biosynthesized AuNPs were stable, hexagonal and spherical shaped with a size ∼32.5 ± 0.25 nm. The AuNPs and drug conjugated AuNPs showed potential antibacterial and antifungal activity against the oral pathogens. Minimum Inhibitory Concentration (MIC) values of biogenic AuNPs were observed in the range of 6.25–25 μg/mL against selected oral pathogens. Overall, we conclude that biogenic drug delivery system for AZM and CLR can be exploited as potential antimicrobial therapy in future, subject to detailed in-vitro and in-vivo cytotoxicity. Graphical abstract: Overall scheme of the study for the phytosynthesis of AuNPs, its drug blending and potential synergistic anti-microbial activity. Highlights: Green synthesis of AuNPs from Justicia glauca plant extract. AuNPs were blended with Azithromycin and Clarithromycin. AuNPs shows an antagonistic effect with antibiotics against oral pathogens.